Clinician and Patient Factors Influencing Treatment Decisions: Ethnographic Study of Antibiotic Prescribing and Operative Procedures in Out-of-Hours and General Dental Practices - Wendy Thompson; Rosemary McEachan; Susan Pavitt; Gail Douglas; Marion Bowman; Jenny Boards; Jonathan Sandoe (MDPI AG, 2020)
Operative treatment is indicated for most toothache/dental abscesses, yet antibiotics instead of procedures are often prescribed. This ethnographic study aimed to identify clinician and patient factors influencing urgent dental care for adults during actual appointments; and to identify elements sensitive to context. Appointments were observed in out-of-hours and general dental practices. Follow-up interviews took place with dentists, dental nurses, and patients. Dentist and patient factors were identified through thematic analysis of observation records and appointment/interview transcripts. Dentist factors were based on a published list of factors influencing antibiotic prescribing for adults with acute conditions across primary health care and presented within the Capability-Opportunity-Motivation-Behaviour model. Contextually sensitive elements were revealed by comparing the factors between settings. In total, thirty-one dentist factors and nineteen patient factors were identified. Beliefs about antibiotics, goals for the appointment and access to dental services were important for both dentists and patients. Dentist factors included beliefs about the lifetime impact of urgent dental procedures on patients. Patient factors included their communication and negotiation skills. Contextual elements included dentists' concerns about inflicting pain on regular patients in general dental practice; and patients' difficulties accessing care to complete temporary treatment provided out of hours. This improved understanding of factors influencing shared decisions about treatments presents significant opportunity for new, evidence-based, contextually sensitive antibiotic stewardship interventions.